NeuroWell: AI-Powered Wearable & Therapy Hub for Mental Health - Dr. Pooja Sahni; Ms. Rachna Manchanda; Dr. Rinkesh Mittal; Ms. Nidhi Chahal; Annaya Singh; Aryan Goyal; Aryan Rathee (International Journal of Brain Sciences, 2026)
Mental health problems such as anxiety, depression, PTSD and sleep disorders affect millions of people worldwide and are a major burden on health systems, with traditional treatment methods usually leading to suboptimal outcomes due to a lack of real-time monitoring, individual intervention or availability. NeuroWell is a cutting-edge artificial intelligence platform combining bio-sensing, neurostimulation and digital therapy into a single mental health support system, using state-of-the-art technologies like EEG, HRV and AI to continuously assess emotions and propose adaptive therapies through virtual reality therapy and haptic feedback. NeuroWell aims to improve patient outcomes, reduce healthcare costs and democratize mental health services by providing remote patient monitoring and individualized treatment. NeuroWell seeks to enhance patient outcomes, lessen healthcare costs, and democratize mental health services by providing remote patient monitoring and individualized care. The growing need for creative mental health solutions around the world supports the viability of this study, which is a significant and timely development in digital mental healthcare.
Keywords: AI; EEG; GSR; HRV; Mental health; VR therapy; bio-sensing; neurostimulation